Disparitas Pembatalan Akta Pengikatan Jual Beli yang dibuat Atas Dasar Utang Piutang: (Studi Putusan No. 364/Pdt.G/2016/Pn.Jkt.Sel Jo Putusan 539 Pk/Pdt/2020 dan Putusan 23/Pdt.G/2018/Pn.Dpu Jo Putusan No. 1615 K/Pdt/2020) - Ryan Apriliandi; Sutiarnoto Sutiarnoto; Suhaidi Suhaidi (CV Rewang Rencang, 2025)
The Sale and Purchase Binding Agreement (PPJB) is a preliminary agreement made before the execution of the Sale and Purchase Deed to transfer land rights. However, in practice, it is often misused as a guarantee for the settlement of debts, resulting in legal uncertainty. This normative juridical research analyzes the legal standing of debt-based PPJB and finds that such agreements are null and void because they deviate from their original function. Therefore, legal protection is only available through repressive means in the form of a lawsuit for cancellation to the court. An analysis of two court decisions shows that judges will cancel the PPJB if it is proven to contain elements of debt (as in Decision No. 23/Pdt.G/2018/PN.Dpu Jo Decision No. 1615 K/Pdt/2020), but will not cancel it if there is no proven element of debt (as in Decision No. 364/Pdt.G/2016/PN.JKT.Sel Jo Decision No. 539 PK/Pdt/2020). This research concludes that to avoid legal problems, debt relationships should be set forth in a separate debt agreement deed that clearly regulates the rights and obligations of the parties, not through a PPJB which can be detrimental and does not provide legal certainty.